Carbon‐Based Substrates for Highly Dispersed Nanoparticle and Even Single‐Atom Electrocatalysts. Issue 9 (28th March 2019) - Chen, Ya‐Nan; Zhang, Xu; Zhou, Zhen
Abstract: In recent decades, electrocatalysis has become an important research hotspot in energy storage and conversion technologies due to the persistently increasing energy and environmental issues. Nanostructured carbon materials with excellent electrical conductivity, competitive activity, and relatively high chemical stability are extensively studied as either electrocatalysts or substrates to support metal‐based catalysts. Especially, when used as supporting substrates for metal‐based catalysts, carbon‐based materials can not only effectively promote the dispersion of metals and even lead to single‐atom catalysts but also lead to prominent synergistic effects for enhanced activity. This review sheds light on state‐of‐the‐art carbon‐based materials employed as supporting substrates for selected electrocatalytic processes involving H2 /O2 /CO2 /N2 . By combining experimental explorations with theoretical computations, clear insight is elaborately afforded into the fundamental relationship between electrocatalytic activity and metal–substrate interaction, in order to disclose some clues for electrocatalyst design. Finally, the remaining challenges and perspectives are discussed for the future development of carbon‐supported electrocatalysts. Abstract : This review mainly focuses on state‐of art carbon‐based materials involving carbon, C3 N4, C2 N, and B4 C employed as supporting substrates for electrocatalysis. Computations complement the deficiency of experimental techniques, elucidating the electrocatalytic mechanisms through electron transfer, adsorption energy, precise active sites, and metal–substrate interaction.